Compartment Niche Shapes the Assembly and Network of Cannabis sativa-Associated Microbiome - Wei, Guangfei; Ning, Kang; Zhang, Guozhuang; Yu, Haibin; Yang, Shuming; Dai, Fei; Dong, Linlin; Chen, Shilin (Frontiers in Microbiology, 2021)
Interactions between plants and microbes may promote the growth of plants and regulate the production of secondary metabolites. Hemp (Cannabis sativa) is an annual herb and an important commercial crop. However, the assembly and network of hemp-associated microbiomes inhabiting in soil and plant compartments have not been comprehensively understood. This work investigated the assembly and network of bacterial and fungal communities living in soils (bulk and rhizosphere) and plant compartments (root, stem, leaf, and flower) of four hemp ecotypes cultivated in the same habitat. Microbiome assembly was predominantly shaped by compartment niche. Microbial alpha diversity was the highest in soil, continually decreased from root to flower. Core bacterial genera Pseudomonas, Bacillus, Rhizobium, Planococcus, and Sphingomonas were mostly enriched in aerial endosphere niches; Clitopilus, Plectosphaerella and Mortierella were enriched in belowground endosphere. Microbial network complexity and connectivity decreased from root to flower. According to source tracking analysis, hemp microbiota primarily originated from soil and were subsequently filtered in different plant compartments. This work provides details on hemp-associated microbiome along the soil–plant continuum and a comprehensive understanding of the origin and transmission mode of endophytes in hemp.